Network monitoring and control for Radio Televisyen Malaysia (RTM) using software defined network (SDN) / Mohd Nasrulddin Abd Latif - Abd Latif, Mohd Nasrulddin (2016)
The demand of network monitoring and management become more challenging to network engineer especially for governments and privates sector including financial institutions. Current practice that has been used to manage network is by manually configure the IP using traditional ways. It can become more complex and hard to manage if there no proper documentation, poor network designs structures and large scale network infrastructure. It is hard to manage according to predefine policies or to make changes to an existing network. The worst scenario can be happen to network engineer if the current network are been integrated and the bundle of data planes in the network. Software-Defined Networking (SDN) is the solution that can help network engineer to manage their network. By using SDN, it helps us to centralize the network control, simplify network management and even can able to program our network. In current RTM environment, streaming video and audio via internet become more important. Handling multi connection and many clients accessing to the centralized online server may cause of latency and delay because of limited of bandwidth. To provide a greater bandwidth, uninterrupted service and best user experiment, we need one mechanism to handle huge traffic request from users. The servers can be optimize and improve the connectivity between server and network switches by leverage multi Network Interface Card (NICs) that has been installed on multiple servers. In this research, it will apply with Software Defined Networking (SDN). The OpenFlow-based SDN is able to provide a greater bandwidth and do traffic prioritization and dynamic path-selection in multi path environment. A program will be developed to instruct the OpenFlow-based SDN Controller for route modification. The evaluation of the SDN approach will be conducted by comparative study between current network in RTM environment and proposed SDN infrastructure.